The Incidence of Deathbed Communications and Their Impact on the Dying Process. (November 2013) - Lawrence, Madelaine; Repede, Elizabeth
The purpose of this study was to determine the incidence of deathbed communications (DBCs) during the 30 days before death and their impact on the dying process. A total of 60 hospice chart audits and 75 survey responses by hospice nurses across the United States were analyzed. Chart audits revealed 5 (8.33%) of the 60 included descriptions of DBCs. The survey of 75 hospice nurses identified 363 incidences of DBCs, with an average of 4.8 patient occurrences per nurse per 30 days. In all, 89% of the hospice nurses reported patients who experienced a DBC had a peaceful and calm death, with only 40.5% reporting a peaceful and calm death without the DBC. These DBCs have a positive impact on the dying process but are underreported in patient records and under described in textbooks.